Characterization of the putative operon containing arylamine N−acetyltransferase (nat) in Mycobacterium bovis BCG - Eltis, E (2006)
Mycobacterium bovis BCG and Mycobacterium tuberculosis possess a single arylamine N-acetyltransferase whose gene is predicted to occur within a six-gene operon. Deletion of the nat gene caused an extended lag phase in M. bovis BCG and a cell morphology associated with an altered pattern of cell wall mycolates. Analysis of cDNA from M. bovis BCG shows that during in vitro growth all the genes in the putative nat operon are expressed and the open reading frames are contiguous, supporting the existence of an operon. Two genes in the operon, Mb3599c and Mb3600c, are predicted to encode homologues of enzymes annotated as a 2,3-dihydroxybiphenyl 1,2-dioxygenase (bphC5) and a 2-hydroxy-6-oxo-6-phenylhexa-2,4-dienoate hydrolase (bphD2), respectively, in Rhodococcus RHA1. As predicted, M. bovis BCG cell lysates metabolized the BphC substrate 2,3-dihydroxybiphenyl (2,3-DHB) to 2-hydroxy-6-oxo-6-phenylhexa-2,4-dienoic acid (HOPDA), a BphD substrate, which was subsequently hydrolysed. Immunoprecipitation of the BphD homologue from these lysates led to an accumulation of HOPDA. M. bovis BCG growth on both solid and liquid media was inhibited with either 2,3-DHB or an inhibitor of BphC, 3-chlorocatechol (3-CC). In addition, incubation with 2,3-DHB affects the lipid composition of the cell wall resulting in a diminished level of mycolates and an altered cell morphology similar to the Δnat strain. We propose the enzymes encoded by the putative operon have a similar endogenous role to that of the NAT enzyme and are part of a pathway important for cell wall synthesis.